(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
The teaching of specialized terminology in English has become increasingly important due to globalization, academic mobility, and the growing demand for professional communication skills. Specialized terminology constitutes the core vocabulary of professional discourse and enables learners to participate effectively in specific fields such as medicine, engineering, law, economics, and information technology. This article examines the linguodidactic foundations of teaching specialized English terminology, focusing on theoretical principles, pedagogical approaches, and effective instructional strategies. The study highlights the role of communicative competence, contextual learning, and cognitive approaches in facilitating terminology acquisition. Furthermore, it discusses challenges encountered by learners and teachers and proposes recommendations for improving terminology instruction in English for Specific Purposes (ESP) courses.